An overview of the Late Triassic–Pleistocene magmatism in the Golfo San Jorge Basin (Latin American Journal of Sedimentology and Basin Analysis, 2025)
The Patagonian Late Triassic–Pleistocene magmatic history encompasses multiple intraplate and subduction–related events associated with diverse geodynamic settings. Key episodes include the Late Triassic and Late Cretaceous–Paleocene flat slabs, the Cenozoic subduction of two mid-ocean ridges, slab break-off and tearing events during the Jurassic, Cretaceous–Paleocene, and Late Miocene–Pleistocene, as well as the influence of the mantle transition zone from the latest Eocene to the Middle Miocene. These processes collectively triggered significant magmatic episodes across the region. This overview highlights the main features of these magmatic events, their associated geodynamic contexts, and the proposed petrogenetic models, focusing on the central Patagonian region, including the Golfo San Jorge Basin and its surrounding areas.
Keywords: Central Patagonia; Golfo San Jorge Basin; magmatism